P4.18 ANTIHYPERTENSIVE ACTIVITY OF LONG CHAIN FATTY ACID DERIVATIVES OF FLAVONOIDS VIA INHIBITION OF RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM (RAAS) - Bhullar Khushwant Singh; Zia ullah; Rupasinghe Vasantha (Artery Research, 2013)
Hypertension is a contributing factor to pathophysiology of vascular damage and accelerated arterial stiffening. Renin-angiotensin-aldosterone system (RAAS) inhibitors are widely used for treatment of persistent hypertension. Along with conventional antihypertensive therapy, nutritional intervention has also gained attention as arterial and vascular complications are closely associated with dietary and lifestyle risk factors. Flavonoids and omega-3 polyunsaturated fatty acids (PUFA) are the key antihypertensive biomolecules emerging to prevent and manage hypertension. In the current study, twelve long chain fatty acid derivatives of isoquercitrin (Q3G) and phloridzin (PZ) were investigated for inhibition of angiotensin-converting enzyme (ACE), renin and aldosterone synthase in comparison to their parent compounds in vitro. The linoleic and α-linolenic esters of PZ were the strongest (IC50 69.9–70.8 μM) while Q3G and PZ (IC50 >200 μM) were the weakest renin inhibitors in vitro (p<0.05). Similar to renin inhibition, PZ derivatives exhibited stronger ACE inhibition compared to Q3G. The eicosapentaenoic acid (EPA) ester of PZ (IC50 16.03 μM) was the strongest, while PZ (IC50 123.96 μM) was the weakest ACE inhibitor (p<0.05) among all tested compounds. However, all investigated compounds had no effect on aldosterone synthase inhibition (p<0.05). Overall, the results showed that phloridzin derivatives were stronger antihypertensive agents than isoquercitrin. It is indicated from our study that these novel compounds as dual RAAS inhibitors may be used as potent bioactive ingredients to develop functional foods and nutraceuticals for prevention and treatment of high blood pressure.